Civil Wars, Coup d'Etat, Regime Changes: Foreign Projects of Quantitative Analysis - Anna Yurievna Kuznetsova (Vestnik RUDN. International Relations, 2015)
In the given article, the author provides an overview of foreign databases and research tools on internal conflicts, regime changes and revolutionarily transformations. The following projects were reviewed: Polity IV, UCDP Conflict Encyclopedia, Transformation Index BTI 2014, and Conflict Barometer. Among the criteria used to compare these databases: project aims, subject of inquiry, and units of measurement, project chronology, methodology, data collection and processing. The analysis of results has also been compared as well as the advantages and disadvantages of databases under study. Such an analysis demonstrated that despite the projects reputation the operational definitions of these projects are their main problem. Sometimes poor operational definitions affect the country ranking in indexes. Moreover, qualitative variables exceed quantitative variables. In most cases variables depend on subjective estimation of an authoring team. Such a situation means that estimations and country ranking in indexes may be different from each other just because of different approaches of scientists. What is more, it is worth paying attention to some country positions in rankings. Subjective estimations of foreign scientists can not always reflect the real scoring.